LOOPS RELATED TO REFLECTION GEOMETRIES - Karzel, Helmut (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2016)
Dedicated to $Johannes B\ddot{o}hm$ on the occasion of his 90-th birthday.